Efficacy and Safety of Intralesional Immunotherapy with Tuberculin Purified Protein Derivative among Cutaneous Wart Patients - Shrestha, Sanju Babu; Bhusal, Mohan; Jwarchan, Jayanti; Gautam, Sujan; Shrestha, Prashanna Raj (Journal of Nepal Health Research Council, 2023)
Background: Cutaneous warts are common skin problems caused by Human Papilloma Virus. Conventional therapies are mostly ablative and limited by recurrences and side effects. Immunotherapy using bacterial, fungal, and viral antigens is an emerging and safer technique to treat warts at local and distant sites. The objective of this study was to measure the efficacy and safety of intralesional immunotherapy with tuberculin purified protein derivative among cutaneous wart patients in the dermatology department of a tertiary care centre. Methods: A cross sectional, time series design, was conducted between October 2019 and September 2020 among 77 patients of cutaneous warts attending Dermatology out-patient department using convenience sampling. Percentage response was evaluated for patients treated with tuberculin purified protein derivative for eight weeks at an interval of two weeks into complete response (100% clearance), partial response (50-99% clearance), no response (0-49% clearance). Side effects were also recorded. Statistical Package for the Social Sciences version 20.0 was used for data analysis. Results: Out of 77 patients, complete response (100%) was seen in 53.2% patients, partial response (50-99%) in 14.3% and no response (0-49%) was seen in 32.5%. Side effects noted were pain and erythema (19.50%), blisters (2.60%) and flu like symptoms (1.30%). Conclusions: Intralesional PPD is an effective and safer therapeutic option for the treatment of cutaneous warts. Keywords: Immunotherapy; intralesional injections; purified protein derivative of tuberculin; warts